MICROSATELLITE-UNSTABLE COLORECTAL CANCER IN ELDERLY PATIENTS: CLINICAL FEATURES AND THE ROLE OF IMMUNODEFICIENCY - D. V. Pashkov; A. R. Venina; A. O. Ivantsov; G. A. Yanus; G. A. Raskin; E. N. Imyanitov; S. E. Kubrina; A. D. Mikushina; G. M. Manikhas; E. V. Ponomareva; I. I. Dzidzava; A. G. Iyevleva (Сибирский онкологический журнал, 2020)
Background. Tumors demonstrating the phenomenon of microsatellite instability (MSI) represent a special category of colorectal cancer (CRC). Such neoplasms account for up to 20 % of CRC and are characterized by specific molecular and clinical manifestations, including high immunogenicity and sensitivity to immunotherapy. MSI phenotype occurs in two different groups of patients: young individuals with Lynch syndrome and patients older than 70 years with non-hereditary CRC. We assume that the development of sporadic MSI-positive tumors in elderly patients may be associated with age-dependent decrease in immune defense. The aim of the study was to investigate clinical and morphological characteristics in elderly patients with MSI-positive colorectal cancer. Material and methods. MSI status and mutations in the BRAF gene were tested in a group of 384 CRC patients older than 65 years by PCR-based techniques. A comparative analysis of clinico-pathological features was further conducted in the groups of 23 MSI-positive and 34 MSI-negative CRC cases. Results. MSI-positive phenotype was associated with the proximal tumor location, low degree of differentiation and the presence of the mucinous component in the tumor (p<0.0001, p=0.005, and p=0.0001, respectively). Patients with MSI-positive CRC containing BRAF mutations showed a significant prevalence of RhD-negative erythrocyte phenotype (53.3 % vs 11.8 %, p=0.004). In patients with MSI-positive carcinomas, the increased frequency of preoperative leukocytosis (p=0.009) and lymphopenia (p=0.014) was observed. Conclusion. The increased occurrence of Rh-negative erythrocyte phenotype and white blood formula changes in elderly patients with MSI-positive CRC may indicate the role of immune system disorders in the development of microsatellite-unstable carcinomas.